Ethnomusicology in Church Music Education: Revitalizing Batak Musical Values and Practices - Pardede, Boho Parulian (LP. Ma'arif Janggan Magetan, 2024)
This study aims to analyze the role of ethnomusicology in church music education as an effort to revitalize the values and practices of Batak music in the context of contemporary Christian worship. This study uses a literature review approach that examines theories, empirical findings, and cultural practices related to Batak music, church music education, and liturgical inculturation movements. The results of the study show that the dominance of modern spiritual music has shifted the role of Batak music in worship, especially due to changes in the preferences of the younger generation, lack of cultural integration in the theological education curriculum, and the limited number of educators with ethnomusicology competencies. The analysis also revealed that Batak music has significant pedagogical, spiritual, and aesthetic potential as affirmed by Rice, Merriam, and Nettl about the importance of cultural context in musical practice. The findings confirm that culture-based church music education can improve the identity, participation, and liturgical meaning of the congregation. This study addresses a major gap concerning the absence of comprehensive analyses that connect ethnomusicology frameworks with practical church education strategies for Batak music revitalization. This study concludes that the revitalization of Batak music requires a holistic approach involving churches, educational institutions, cultural communities, and traditional musicians to develop a contextual curriculum and model of worship.